The stonefly genus Lednia in North America (Plecoptera: Nemouridae) - Baumann, Richard W. (Illiesia, 2010)
The nemourid genus Lednia is characterized in the male, female and nymph stages. Two new species are described, L. borealis and L. sierra. Illustrations are provided as line drawings and scanning electron microscope images for the adult stages. Three Lednia species are presently known from western North America: L. borealis, Cascade Range, Washington; L. tumana, northern Rocky Mountains and L. sierra, Sierra Nevada, California.
Keywords: entomologija; entomology; Plecoptera; vrbnice; Nemouridae; Lednia; stoneflies; North America